ASA YANG TERSISA: PEMBELAJARAN SASTRA, HALO APA KABAR? SELAYANG PANDANG MELIRIK “DUDUK MASALAH” (ANTARA HARAPAN DAN KENYATAAN) - Udjang Pairin (Universitas Negeri Surabaya, 2022)
Literary works are the result of the writer's deepest contemplation about life and life. With the sharpness of his imagination, the portrait of life is naturally elaborated in romances, novels, poetry, and so on so that it is presented like a real, concrete picture and anesthetizes the reader. Studying literature well can educate readers. Everything about life experiences can be explored critically and creatively. And that is the main mission of learning literature that literature teachers need to develop. With the limited ability of teachers and the allocation of time, educators and curriculum designers must determine the vision and mission of the direction of teaching literature in a directed, measurable, and correct manner. With the improved 2013 curriculum, teachers and schools have ample opportunities to be creative in how to improve the ethos of learning literature that is interesting, innovative, and conducive. One of the models that can be developed is with a priority, pragmatic approach, a material selection process that is tailored to the conditions of the learner's interests, and measurable, fun, and controlled tasks. Alternative solutions that can be taken so that literature learning is getting better can be maximized through; 1) The role of MGMP, 2) maximizing other supports, 3) accelerating technology by literature teachers, 4) schools as literary fields, 5) innovative learning, 6) literary practice to literary theory, 7) recreational traditions replace the pedantic tradition, 8) maximizing school autonomy, 9) and time allocation considerations. Keywords: Literature learning, Indonesian curriculum, problems, between expectations and reality.